2015
DOI: 10.1590/0104-1428.1986
|View full text |Cite
|
Sign up to set email alerts
|

Biobased additive plasticizing Polylactic acid (PLA)

Abstract: SbstractPolylactic acid (PLA) is an attractive candidate for replacing petrochemical polymers because it is from renewable resources. In this study, a specific PLA 2002D was melt-mixed with two plasticizers: triethyl citrate (TEC) and acetyl tributyl citrate (ATBC). The plasticized PLA with various concentrations were analyzed by differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), melt flow index (MFI), thermogravimetric analysis (TGA), X-ray diffraction (XRD), UV-Visible spectroscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 32 publications
5
113
1
2
Order By: Relevance
“…The DSC curve of PLA showed T g , T cc , and T m at 62, 101, and 174 C, respectively, which are typical of semicrystalline polymers and similar to values reported in the literature. 9 Maiza et al 4 reported the same trend in their study of the plasticizing effect of TEC on the properties of PLA; they observed that T g decreased with an increase in the TEC content. This lowering of T g , T cc , and T m of PLA is attributed to the plasticizing effect of the plasticizer, that is, TEC.…”
Section: Evaluation Of Lamellar Arrangements Of Pla-tec In Presence Omentioning
confidence: 59%
See 1 more Smart Citation
“…The DSC curve of PLA showed T g , T cc , and T m at 62, 101, and 174 C, respectively, which are typical of semicrystalline polymers and similar to values reported in the literature. 9 Maiza et al 4 reported the same trend in their study of the plasticizing effect of TEC on the properties of PLA; they observed that T g decreased with an increase in the TEC content. This lowering of T g , T cc , and T m of PLA is attributed to the plasticizing effect of the plasticizer, that is, TEC.…”
Section: Evaluation Of Lamellar Arrangements Of Pla-tec In Presence Omentioning
confidence: 59%
“…4 Plasticizers promote the growth rate of crystallites 5 and act as processing aids 6 ; they also enhance the flexibility and ductility of polymer materials. 4 Plasticizers promote the growth rate of crystallites 5 and act as processing aids 6 ; they also enhance the flexibility and ductility of polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its low molecular size, the plasticizer occupied the intermolecular spaces between the polymer chains. It reduced the energy for molecular motion and the formation of hydrogen bonding between the polymer chains and increased the free volume and molecular mobility . The addition of ATBC also affected T m and X c .…”
Section: Resultsmentioning
confidence: 87%
“…PLA was dried at 80 °C for 24 h in a vacuum oven before it was processed by melt blending . Materials with various formulations (Table ) were used to prepare the composites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation